ARTP statement on pulmonary function testing 2020. Issue 1 (5th July 2020) - Sylvester, Karl Peter; Clayton, Nigel; Cliff, Ian; Hepple, Michael; Kendrick, Adrian; Kirkby, Jane; Miller, Martin; Moore, Alan; Rafferty, Gerrard Francis; O'Reilly, Liam; Shakespeare, Joanna; Smith, Laurie; et al.
Abstract : The Association for Respiratory Technology & Physiology (ARTP) last produced a statement on the performance of lung function testing in 1994. At that time the focus was on a practical statement for people working in lung function laboratories. Since that time there have been many technological advances and alterations to best practice in the measurement and interpretation of lung function assessments. In light of these advances an update was warranted. ARTP, therefore, have provided within this document, where available, the most up-to-date and evidence-based recommendations for the most common lung function assessments performed in laboratories across the UK. These recommendations set out the requirements and considerations that need to be made in terms of environmental and patient factors that may influence both the performance and interpretation of lung function tests. They also incorporate procedures to ensure quality assured diagnostic investigations that include those associated with equipment, the healthcare professional conducting the assessments and the results achieved by the subject. Each section aims to outline the common parameters provided for each investigation, a brief principle behind the measurements (where applicable), and suggested acceptability and reproducibility criteria.